Presumption of Innocence Against Criminal Offenders in the Police: A Critical Study - Oktavia Wulandari; Ali Imron; Briliyan Ernawati; Nazar Nurdin (Walisongo Law Review (Walrev), 2020)
The purpose of this paper is to conduct a critical study of the application of the presumption of innocence to the perpetrators of criminal acts (suspects) investigated by the police. Implementation of the principle is important to study because the suspect must not be considered guilty before the criminal act is proven. A review of this case was carried out at the Kendal Police Department in mid-2019-2020. Writing texts are written with a normative-empirical approach. The non-doctrinal approach was chosen because it can clearly examine the application of the principle of presumption of innocence in more depth. Therefore, the author considers it necessary to carefully examine the application of these principles in the process of law enforcement at the police level. The results showed that the application of the principle of presumption of innocence in the Kendal Police Department was not optimal, because some of its applications were colored by threats and acts of violence. The suboptimal application of this principle is influenced by various factors, including the lack of legal knowledge of suspects and threats and acts of violence that are not reported. As we know the presumption of innocence is a fundamental principle in the criminal justice system, where a person must be positioned innocent before his guilt is proven in an honest and open trial.